Penerapan Green Accounting dalam Perusahaan untuk Mendukung Pembangunan Berkelanjutan Bersama PT CP - Weruin, Urbanus Ura (Universitas Pahlawan Tuanku Tambusai, 2026)
Green accounting is an approach that incorporates environmental sustainability considerations into company policy, particularly in relation to the use of natural, social, and financial resources. The objective of this PKM is to encourage PT CP to begin taking into account the environmental impact of all its business activities so that they are in line with the principles of sustainable development. The methods used include the identification, measurement, assessment, and disclosure of environmental and social costs related to the company's productive activities. This approach is carried out through mentoring, production process analysis, and financial statement evaluation so that the company understands the importance of long-term efficiency and social responsibility. The results of the PKM show an increase in the awareness of PT CP managers regarding the urgency of implementing green accounting, especially amid global environmental crises such as climate change and land degradation. This awareness is the first step for the company towards more sustainable business practices.